Belize : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This paper highlights the stock of recent developments in Belize's financial system. The financial system remains sizable, at 157 percent of GDP in March 2017. The importance of macrofinancial linkages justifies their continuous monitoring, not only for financial stability but also for overall macroeconomic stability. Both domestic and international banks play important roles in mobilizing savings for domestic investment and in facilitating external trade, on which the small open economy of Belize strongly depends. The financial intermediation role of offshore banks has declined in recent years. Offshore banks receive deposits in foreign currency from nonresidents, and lend to foreign investors, and domestic businesses, mostly in the real estate and tourism sectors. The Central Bank of Belize (CBB) is committed to securing financial system soundness. It conducted 5 on-site examinations in 2016, including 3 full-scope examinations for two domestic banks, and one credit union.